Identifying patterns in the effect exerted by a cooling process and the fine grinding modes on the qualitative indicators of a meat and bone paste - Kakimov, Aitbek; Kabdylzhar, Baktybala; Yessimbekov, Zhanibek; Suychinov, Anuarbek; Baikadamova, Asemgul (Eastern-European Journal of Enterprise Technologies, 2020)
This paper describes a technology for obtaining a homogeneous meat and bone paste made through a multi-stage grinding at a chopper grinder and the micro-grinder "Supermasscolloider". The relevance of the study relates to that the meat and bone raw materials are processed for food purposes, thereby improving a non-waste technology in the meat processing industry. The effect of a cooling process and the parameters of fine grinding on the quality indicators and the microstructure of meat and bone paste after grinding has been studied. The research results have established that a decrease in the diameter of a chopper grinder's mesh leads to an increase in the temperature of meat and bone mince, from 16 °C to 26 °C. A change in the temperature of output raw materials has been investigated at the micro-grinder "Supermasscolloider" with different gaps between the grinding wheels (0.25 mm, 0.10 mm, 0.02 mm), depending on the amount of added water. It has been established that following the grinding at a micro-grinder with the addition of water the temperature of the raw materials at the output decreased, at gaps of 0.25 mm and 0.10 mm, from 34 °C to 17 °C; at a gap of 0.02 mm ‒ from 37 °C to 19 °C. When studying the functional and technological properties of a meat and bone paste with the addition of 50 % of water, it was found that the meat and bone paste had high moisture-binding (75.63 %) and fat-retaining (73.38 %) capacities. The moisture-binding capacity of the meat and bone paste was 65.3 %, the emulsifying capacity was 55.8 %. The microstructure and granulometric composition of the meat and bone paste with the addition of 50 % of water have been studied. The result of the conducted analysis of the geometric dimensions of bone particles has revealed that when the minced meat and bone are processed at a micro-grinder, the size of the bone particles was within the set gaps between the grinding wheels, while the consistency of the meat and bone paste was uniform and ointment-like